The Profile of Short Vowel ‘A’ in Japanese Language that Determines the Meaning as Pronounced by University Students in Indonesia - Febriyanti, Rike (Lingua Cultura, 2023)
The research discussed that certain sounds, like the short vowel ‘a’, which was entirely different from the long vowel ‘a’, were specific to Japanese and had distinct meanings from those of Indonesian. As a result, 60 students majoring in Japanese language instruction from six Indonesian universities were interviewed face-to-face and recorded. Native speakers of the Japanese language were requested to record their voices using the short vowel ‘a’ as the students’ sound reference. After that, the students were asked to identify and produce the short vowel ‘a’. PRAAT was then used to analyze the students’ recordings. Additionally, the students’ sounds were contrasted with those of Japanese native speakers. The spectrogram analysis clearly shows that students are still having trouble telling the difference between the long vowel ‘a’ (OBAASAN) and the short vowel ‘a’ (OBAASAN) because they produce significantly longer short vowels ‘a’ that are almost as long as double vowel ‘a’. This is highly likely to occur since Japanese language learners are not taught to deliberately recognize the distinct sounds, such as the long and short vowels ‘a’, that distinguish the language’s meanings. In addition, their low frequency and energy density of pronunciation of the short vowel ‘a’ suggest they are less confident in their pronunciation.